Splendours of the Sun King: the construction of Louis XIV's glory in the visual arts - Walton, David Edward / DE (2024)
This dissertation explores how visual artists willingly helped create the glory of Louis XIV of France, starting with the period’s iconic image created by Hyacinthe Rigaud’s painting of Louis in Coronation Robes, a larger-than-life work summing up Absolutist splendour. Furthermore, sculptures of the king demonstrated his ability to crush political and religious enemies, while equine sculptures illustrated Louis’s mastery of his horse, which by implication showed his authority over his subjects. Sculpture in the form of medals and coins formed part of a fabricated personal history intended for Louis’s future reputation. Engraved prints of monumental history paintings distributed internationally ensured Louis’s renown. In the second part, this study seeks to show how Louis’s propaganda was served by the creation of the Academy of Painting and Sculpture and how artists had to conform to the snobbery of court life. When Louis XIV aligned himself with past heroes such as Alexander the Great in monumental scenes of glory, court artists were required to study ancient texts, informing themselves on theories of classical composition, gesture, deportment, and colour. In the final part, the study investigates Louis’s dynastic persona as the Sun King through the mythology of Apollo and how this pagan role balanced with Louis’s portrayal as the most Christian king.